2006
DOI: 10.1089/apc.2006.20.637
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Adherence to Highly Active Antiretroviral Therapy and Protected Sex Among People Living with HIV/AIDS: The Role of Patient–Provider Communication in Rio De Janeiro, Brazil

Abstract: This exploratory study examined patient-provider communication dynamics regarding adherence to highly active antiretroviral therapy (HAART) and protective sexual behavior among people living with HIV/AIDS (PLWHA). We conducted 20 direct observations of routine consultations between PLWHA and care providers in two large public health clinics providing free HIV medications and clinical care to PLWHA in the greater Rio de Janeiro area of Brazil. Immediately after these observations, 20 semistructured in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
3
18
0
1
Order By: Relevance
“…While data on actual communication in Brazil is not available for comparison, 33% of women in highly urban São Paulo [2] and 88% of women in Fortaleza [1] anticipated a negative response from their provider regarding childbearing desires. Although no direct questions regarding childbearing were asked, a 2006 study in Rio de Janeiro observing provider communication in the context of ART adherence noted communication regarding safe sexual practices was rare and occurred only in cases when patients presented with STI symptoms or were thought to be pregnant [45].…”
Section: Discussionmentioning
confidence: 99%
“…While data on actual communication in Brazil is not available for comparison, 33% of women in highly urban São Paulo [2] and 88% of women in Fortaleza [1] anticipated a negative response from their provider regarding childbearing desires. Although no direct questions regarding childbearing were asked, a 2006 study in Rio de Janeiro observing provider communication in the context of ART adherence noted communication regarding safe sexual practices was rare and occurred only in cases when patients presented with STI symptoms or were thought to be pregnant [45].…”
Section: Discussionmentioning
confidence: 99%
“…Outro aspecto destacado na literatura é a importância de uma postura empática e apoiadora dos profissionais de saúde para o ajustamento psicológico dos pacientes vivendo com HIV (Fehringer et al, 2006;Sanders, 2008). Nesse sentido, os relatos das mães do presente estudo revelaram tanto aspectos positivos quanto negativos.…”
Section: Discussionunclassified
“…These are not new problems, as they have been indicated by other authors in their previous studies who concluded that being understaffed is a challenge, but it does not justify the lack of provision of services [57,58]. Of late, changes in the health care system have put more responsibility on patients to be active participants in decision making, self-care, and disease management.…”
Section: Information Flowmentioning
confidence: 99%